Nucleophilic Reactivities of Bis‐Acceptor‐Substituted Benzyl Anions. Issue 8 (28th February 2017) - Puente, Ángel; Ofial, Armin R.; Mayr, Herbert
Abstract : The kinetics of the reactions of bis‐acceptor‐substituted benzyl anions (PhCXY –, X, Y = CN, CO2 Et, COPh, SO2 Ph) with benzhydrylium ions and quinone methides (reference electrophiles) have been determined in dimethyl sulfoxide solution at 20 °C. The reactions follow second‐order kinetics, first order with respect to the electrophile and first order with respect to the carbanion. The addition of 18‐crown‐6 ether, which efficiently coordinates to the anions' counter ions K +, did not affect the kinetics, which indicates that the measured rate constants refer to the reactivities of the nonpaired carbanions. Comparison with the reactivities of the structurally analogous secondary carbanions HCXY – shows that replacement of H at the carbanionic center by Ph reduces the nucleophilic reactivities towards a reference benzhydrylium ion by factors in the range of only 1.2 (X, Y = SO2 Ph) to 6 (X, Y = CO2 Et). The plots of lg k 2 versus the electrophilicity parameters E of the reference electrophiles are linear, thereby indicating that the correlation lg k 2 (20 °C) = s N ( E + N ), which characterizes nucleophiles by the two solvent‐dependent parameters s N and N and electrophiles by the parameter E, is applicable. In this way, it becomes possible to integrate these carbanions into our comprehensive nucleophilicity scale, which provides a direct comparison of the nucleophilic reactivities of different families of compounds. Abstract : The kinetics of the reactions of bis‐acceptor‐substituted benzylic anions with a set of reference electrophiles has been followed in DMSO at 20 °C. The linear free‐energy relationship in Equation (1) was used to derive the nucleophilicity descriptors N and s N for the title compounds from the reported experimental rate constants.